Functions of the soil organisms in the grassland ecosystem - Crespo, Gustavo (Cuban Journal of Agricultural Science, 2013)
An update in the progress of the scientific researches related to the functions of the soil organisms in the grassland ecosystem is shown. The performance of different microorganisms in this ecosystem is recognized, focusing, mainly, on the functions of primary decomposers, like beetles, worms and termites. It is emphasized that these organisms, responsible for decomposing the excretions of mammals and the litter of the grasslands, increase the general fertility of soils and grassland productivity. The interactions between the primary decomposers and the microorganisms, which live in their gastrointestinal track and in the soil, are determinant in the functioning of this ecosystem. Worms, beetles, and termites have an important function in recycling nutrients in ecosystems of well-managed grasslands. Key words: organisms, soil, grassland, interactions.